On the relationship between acculturation and intercultural understanding: Insight from the Reading the Mind in the Eyes test. (May 2016) - Bjornsdottir, R. Thora; Rule, Nicholas O.
Abstract: Previous research has repeatedly demonstrated the importance of culture and cultural identification to interpersonal understanding. We aimed to apply the ideas from this domain to mental state reasoning, or theory of mind. We thus investigated the relationship between acculturation and inferring the mental states of other people within and across cultures by measuring Caucasian and East Asian participants' accuracy in inferring the mental states of own- and other-ethnicity targets using the Reading the Mind in the Eyes test. As expected, Caucasian participants showed a significant ingroup advantage in inferring the mental states of own- versus other-ethnicity targets but no variation according to measures of acculturation. More important, East Asian residents of Canada showed greater accuracy for own- versus other-ethnicity targets—and their accuracy for Caucasian targets increased as a function of (i) the time they had lived in Canada, (ii) their experience interacting with Caucasians, (iii) increased endorsement of mainstream Canadian values, and (iv) decreased endorsement of their heritage culture's values. These results suggest that cross-cultural understanding may be malleable to acculturation and cultural experience, highlighting the importance of further research on how people from different cultural perspectives come to understand each other and subsequently ameliorate cross-cultural misunderstanding.